UNDERSTANDING AND USING EMOTIONS IN MARKETING - Mirela-Cristina VOICU (Challenges of the Knowledge Society)
Emotion always had a special power, influencing the decisions of individuals and causing them to act in one way or another. In classical economic theory, consumers play the role of rational individuals making decisions based only on relevant information using conscious thinking. Unfortunately, conscious thinking requires a significant amount of energy from the individual, which has led to the evolution of the human body by limiting this type of thinking, to increase efficiency. Thus, the human brain has come to process unconsciously almost all communication signals in the environment (visual, auditory, tactile, etc.), through implicit processes controlled by the limbic system ("the emotional brain"). As a result, many consumer decisions are made unconsciously and are based on emotions. It is also well known that consumers' purchasing decisions are driven by two types of needs: functional needs, satisfied through product functions, and emotional needs associated with the psychological aspects of product possession. Emotion is one of the most important motivators for purchasing, representing an important strategic element in the organization's marketing activity, giving meaning and depth to the experience with a brand or a product. In the age of strategic-relationship marketing, emotion plays a key role. In this context, the following paper reveals important aspects regarding the necessity of understanding how emotions influence consumer behavior together with ways in which emotions can be used in the company’s marketing activity.